The impact of widespread regulatory neofunctionalization on homeolog gene evolution following whole-genome duplication in maize. - Hughes, T; Langdale, J; Kelly, S; Kelly, S (Cold Spring Harbor Laboratory Press, 2014)
Whole-genome duplications are a widespread feature of plant genome evolution, having been detected in all flowering plant lineages. Despite the prevalence of these events, the extent to which duplicated genes (homeolog gene pairs) functionally diverge (neofunctionalization) is unclear. We present a genome-wide analysis of molecular evolution and regulatory neofunctionalization in maize (Zea mays L.). We demonstrate that 13% of all homeolog gene pairs in maize are regulatory neofunctionalized in leaves, and that regulatory neofunctionalized genes experience enhanced purifying selection. We show that significantly more genes have been regulatory neofunctionalized in foliar leaves than in husk leaves and that both leaf types have experienced selection for distinct functional roles. Furthermore, we demonstrate that biased subgenome expression dominance occurs only in the presence of regulatory neofunctionalization and that in nonregulatory neofunctionalized genes subgenome dominance is progressively acquired during development. Taken together, our study reveals several novel insights into the evolution of maize, genes, and gene expression, and provides a general model for gene evolution following whole-genome duplication in plants.